1980
DOI: 10.1039/an9800500756
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of trace concentrations of arsenic, antimony and bismuth in soils and sediments by volatile hydride generation and inductively coupled plasma emission spectrometry

Abstract: Trace amounts of arsenic, antimony and bismuth in soils and sediments are determined simultaneously by an inductively coupled plasmavolatile hydride method after rapid attack with concentrated hydrochloric acid in sealed tubes. The samples are treated with the acid a t 150 "C for 2 h in capped test-tubes. After addition of potassium iodide solution, the hydrides are formed by mixing the solution with sodium tetrahydroborate(II1) solution in a continuousflow system, and are swept into the plasma by a stream of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…As shown in Figure 2, higher sensitivity is achieved for As(II1) and Sb(II1) than for As(V) and Sb(V), although for arsenic the improvement is only about 2-fold. Several previous workers (9,12,16) have reported the reduction of As(V) and Sb(V) to the 3+ oxidation state, prior to the hydride generation, by the addition of a potassium iodide solution. In the permitting simultaneous determination of As(II1) and Sb(III), but not selenium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2, higher sensitivity is achieved for As(II1) and Sb(II1) than for As(V) and Sb(V), although for arsenic the improvement is only about 2-fold. Several previous workers (9,12,16) have reported the reduction of As(V) and Sb(V) to the 3+ oxidation state, prior to the hydride generation, by the addition of a potassium iodide solution. In the permitting simultaneous determination of As(II1) and Sb(III), but not selenium.…”
Section: Resultsmentioning
confidence: 99%
“…For this and other reasons Thompson and co-workers found it necessary to develop a separate procedure for the Present address: Instituto de Quimica, Universidade de SBo Paulo, Caixa Postal 20780, SHo Paulo, Brasil. determination of selenium in soils and sediments (10) although arsenic, antimony, aind bismuth could be determined simultaneously (9). Recently, a method for simultaneous determination of As(III), SSb(III), and Se(1V) in water samples was reported in which the problem of reduction of Se(1V) to Se(0) by potassium iodide was circumvented by adding the potassium iodide after the addition of sodium borohydride (16).…”
mentioning
confidence: 99%
“…36 The use of HCl has the added advantage of dissolving common iron and silica minerals and apatite. 37 We have evaluated the use of HNO3-HCl mixtures for releasing Sb from mine contaminated sediments 38 and found Sb is nearly quantitatively extracted (using a 2:…”
Section: Biotamentioning
confidence: 99%
“…The use of elevated temperature (150 o C) enhances the dissolution of Sb containing phases. 37 In these sediments, Sb is adsorbed to Fe/Mn oxyhydroxides or silicates. [38][39][40] More recently, the use of a using a 3:1 v/v HNO3-HCl mixture has given good recoveries (>93%) from a certified stream sediment.…”
Section: Biotamentioning
confidence: 99%
“…Previous work on the composition of coffee and its products is mainly concerned with the mineral contents and studies on toxic elements are scarcely reported (Clarke et al, 1974;Gillies et al, 1983;Horwitz et al, 1974;Kuennen et al, 1982;Kapur et al, 1974;Koch et al, 1989;Lara et al, 1975/76). No information exists on the content of arsenic and selenium in this product although a number of publications (Goulden et al, 1981;Nakahara et al, 1985;Nakahara, 1981;Nygaard et al, 1982;Oliveira et al, 1983;Pahlavanpour et al, 1980;Ybanez et al, 1992) demonstrated that hydride generation, followed by introduction of gaseous hydrides into an ICP was a suitable method for the determination of several trace elements, including arsenic and selenium, for which detection limits were inadequate for foods and related matrices when conventional pneumatic nebulization was used. The objective of this work was to develop a method for the evaluation of arsenic and selenium in soluble coffee by inductively coupled plasma atomic emission spectrometry with hydride generation in order to attend the Brazilian food legislation.…”
Section: Introductionmentioning
confidence: 99%